LARYNGEAL INFECTIONS IN CHILDREN, OBVIOUS LARYNGITIS WITH DYSPHONIA (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Laryngitis is an inflammation of the voice box (larynx) that causes your child's voice to become raspy or hoarse. Most of the time, laryngitis comes on quickly and lasts as long as 2 weeks. It is caused by overuse, irritation, or infection of the vocal cords inside the larynx. Some of the most common causes are a cold, influenza (flu), or allergies. Below we will focus on laryngeal infections and laryngitis.